Analysis of The Role of Operation Strategy to Create Competitive Advantage Using The SWOT Method at PT Bina Karunia Indonesia - Rizki Suma Pratama; Wiwik Handayani (Kontigensi : Jurnal Ilmiah Manajemen, 2024)
A company needs a strategy, especially in the operational sector which is the heart of a company which has an impact on efficiency and also the quality of the services provided. Business consulting service companies often have operational problems that make it difficult for the company to have a competitive advantage over its competitors. This research aims to identify strengths, weaknesses, opportunities and threats within the company and provide operational strategy solutions for business consulting companies. Data collection was obtained through interviews and questionnaires with the parties involved both internally and externally. The results of this research found that the company needed to develop an operational strategy because there were several problems and it was less efficient. So the researcher made an operational strategy plan based on the competitive advantage of business consulting companies in the city of Surabaya using SWOT analysis. This planning is expected to increase the company's competitiveness.